OBTAINING FORMALDEHYDE RESINS FROM MEA - Kodirova Dilshodhon Tulanovna (American Journals Publishing, 2023)
With the growth of global production, the scope of application of their products is expanding. In this regard, new requirements are being imposed on their quality and waste recycling. At present, the chemical industry has a number of organic waste products that can replace synthetic polymers. After processing this waste, it becomes an adhesive binder with good adhesive properties. Of course, the polymer forms the basis of the glue and the choice of polymer is the first and decisive step in creating the glue. When choosing an adhesive polymer, it is necessary to take into account not only its chemical nature, concept and mutual arrangement of functional groups, but also the molecular weight distribution of poly dispersion and other features of the chemical structure. The use of polymers with a narrow molecular weight distribution ensures the production of adhesives with stable properties.
Keywords: formaldehyde resin, cubic residue of MEA, polarographic method.